PEMANFAATAN TUMBUHAN HUTAN SEBAGAI BAHAN BAKU UNIT USAHA JAMU DAN PENGOLAHAN BAHAN ALAM DI KALIMANTAN SELATAN - Rina Muhayah Noor Pitri (Universitas Lambung Mangkurat, 2016)
The existence of forest plants have been the source of traditional medicine for local communities. The use of natural materials by local communitiies as part of the medicinal treatment is done for subsistence. Not many identifiable utilization of the forest plants to meet the needs of business units herbal raw materials and processing of natural materials. This study seeks to identify the utilization of forest plants as raw material for herbal medicine business unit and the processing of natural materials in South Kalimantan. Mapping the distribution of the manufacturing herbal and natural ingredients also conducted and analyzed its association with the presence of the plant and within the forest. Data is collected using semi-structured interview to further analyzed descriptively. The collection of layers that constitute thematic information for the analysis of Geographic Information Systems. GIS analysis using ArcView 3.3 software. The results showed that the mixture dipterocarp forest is a forest type that is the source material for herbal medicine business unit and the processing of natural materials in South Kalimantan. The business unit is the most widely used natural materials from the forest is the micro and small (≤ 50%) or medium sized business units are relatively few industries using natural materials from the forest (± 10%). The distribution of herbal medicine business unit and the processing of natural materials in South Kalimantan uneven. Herbal medicine business unit and the processing of natural materials is also limited to the city of Banjarmasin, Martapura, Banjarbaru, Amuntai, Barabai. Distance to the forest as a source of raw materials and distribution of herbal industry/processing of natural materials not correlate significantly. The rapid development of urban economy and cultural factors related to the presence of viscous processing units herbal and natural ingredients.